2020
DOI: 10.4049/jimmunol.1900746
|View full text |Cite
|
Sign up to set email alerts
|

DHEA Inhibits Leukocyte Recruitment through Regulation of the Integrin Antagonist DEL-1

Abstract: Leukocytes are rapidly recruited to sites of inflammation via interactions with the vascular endothelium. The steroid hormone dehydroepiandrosterone (DHEA) exerts anti-inflammatory properties; however, the underlying mechanisms are poorly understood. In this study, we show that an anti-inflammatory mechanism of DHEA involves the regulation of developmental endothelial locus 1 (DEL-1) expression. DEL-1 is a secreted homeostatic factor that inhibits b2-integrin-dependent leukocyte adhesion, and the subsequent le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Additionally, ERM not only reversed the inhibitory effect of IL-17 on C/EBPβ binding to the DEL1 promoter but also elevated C/EBPβ binding over and above its constitutive level (ethanol control treatment) ( Figure 5E). Taken together, ERM not only counteracts the inhibitory effect of IL-17 on the binding activity of C/ EBPβ for the DEL1 promoter, as previously shown for resolvins (20) and DHEA (29), but also can directly enhance the binding of C/EBPβ to the DEL1 promoter.…”
Section: Erm Upregulates Del-1 Mrna and Protein Levels In Vitro And Isupporting
confidence: 75%
See 4 more Smart Citations
“…Additionally, ERM not only reversed the inhibitory effect of IL-17 on C/EBPβ binding to the DEL1 promoter but also elevated C/EBPβ binding over and above its constitutive level (ethanol control treatment) ( Figure 5E). Taken together, ERM not only counteracts the inhibitory effect of IL-17 on the binding activity of C/ EBPβ for the DEL1 promoter, as previously shown for resolvins (20) and DHEA (29), but also can directly enhance the binding of C/EBPβ to the DEL1 promoter.…”
Section: Erm Upregulates Del-1 Mrna and Protein Levels In Vitro And Isupporting
confidence: 75%
“…We have previously shown that DEL-1 expression is severely reduced under inflammatory conditions (15,20,29). Specifically, both IL-17 and TNF diminish DEL-1 expression by targeting C/EBPβ, although their effects are reversed by the proresolving lipid mediator RvD1 and steroid hormone dehydroepiandrosterone (DHEA) (20,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations